Laparoscopic Management of Benign Ovarian Cysts: Three Years Experience in Combined Military Hospital, Dhaka (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Ovarian cyst is a common clinical problem affecting women of all age groups. Laparoscopy should be considered as an alternative to laparotomy in the management of benign ovarian cysts. The aim of this study is to determine the safety, efficacy and outcome of laparoscopic surgery for benign ovarian cysts.Materials and Method: A Prospective observational study has been carried out during the period of Jun 2016 to May 2019 in combined military hospital Dhaka. Total 107 patients who underwent laparoscopic surgery for benign ovarian cysts during this period were included in this study.Results: The maximum number of women was in the 21-30 year- old age groups. Majority were endometriotic cyst (45.79%) followed by perovarian cysts (14.01%) and dermoid cysts (12.14%). The diameter ranges from 4-15 cm.and most of them were unilateral (91.5%). Ovarian cystectomy is the most commonly performed procedure (88.78%). Mean duration of surgery was 62.75 minutes. Complications were also fewer like postoperative fever (22.2%), and trocar site infection.(11.2 %). None of the pts required conversion to laparotomy.Conclusion: With a careful preoperative screening the laparoscopic surgery is a safe and effective treatment for benign ovarian cyst Laparoscopic surgery seems to offer significant advantages such as less adverse effects, reduced hospital stay and better quality of life.JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 209-2012